Oxfordshire Women and Their Children's Health (OxWATCH): protocol for a prospective cohort feasibility study. Issue 11 (9th November 2015) - Harrison, S; Petrovic, G; Chevassut, A; Brook, L; Higgins, N; Kenworthy, Y; Selwood, M; Snelgar, T; Arnold, L; Boardman, H; Heneghan, C; Leeson, P; et al.
Abstract : Introduction: Some specific pregnancy disorders are known to be associated with increased incidence of long-term maternal ill health (eg, gestational diabetes with late onset type 2 diabetes; pre-eclampsia with arterial disease). To what degree these later health conditions are a consequence of the woman's constitution prior to pregnancy rather than pregnancy itself triggering changes in a woman's health is unknown. Additionally, there is little prospective evidence for the impact of pre-pregnancy risk factors on the outcome of pregnancy. To understand the importance of pre-pregnancy health requires the recruitment of women into a long-term cohort study before their first successful pregnancy. The aim of this feasibility study is to test recruitment procedures and acceptability of participation to inform the planning of a future large-scale cohort study. Methods: The prospective cohort feasibility study will recruit nulliparous women aged 18–40 years. Women will be asked to complete a questionnaire to assess the acceptability of our recruitment and data collection procedures. Baseline biophysical, genetic, socioeconomic, behavioural and psychological assessments will be conducted and samples of blood, urine, saliva and DNA will be collected. Recruitment feasibility and retention rates will be assessed. Women who become pregnant will be recalled for pregnancy and postpregnancy assessments. Ethics and dissemination: The study protocol was approved by South Central Portsmouth REC (Ref: 12/SC/0492). The findings from the study will be disseminated through peer reviewed journals, national and international conference presentations and public events. Trial registration number: http://www.clinicaltrials.gov ; NCT02419898 .